Snowmelt Infiltration and Macropore Flow in Frozen Soils: Overview, Knowledge Gaps, and a Conceptual Framework - Mohammed, A.A. (2020)
Nonequilibrium gravity‐driven flow can rapidly transport snowmelt to depths below the frost zone or, alternatively, infiltrated water may refreeze in macropores and restrict preferential flow. As with unfrozen soils, models of water movement in frozen soil that rely solely on diffuse flow concepts cannot adequately represent unsaturated macropore hydraulics. Dual‐domain descriptions of unsaturated flow that explicitly define macropore hydraulic characteristics have been successful under unfrozen conditions but need refinement for frozen soils. In particular, because pore connectivity and hydraulic conductivity are influenced by ice content, modeling schemes specifying macropore–matrix interactions and refreezing of infiltrating water are critical. This review discusses the need for research on the interacting effects of macropore flow and soil freeze–thaw and the integration of these concepts into a framework of coupled heat and water transfer. As a result, it proposes a conceptual model of unsaturated flow in frozen macroporous soils that assumes two interacting domains (macropore and matrix) with distinct water and heat transfer regimes.